Effect of texturization on a-Si:H/c-Si hetero-junctions investigated by PCD and μW-PCD mapping of minority carrier's lifetime. (19th September 2019) - Ben Alaya, C; Dridi Rezgui, B; Aouida, S; Ronda, A; Abbarchi, M; Khirouni, K; Bouaïcha, M
Abstract: In a-Si:H/c-Si hetero-junction solar cells, front surface texturization is used to maximize light absorption, while care should be taken to avoid high number of generated dangling bonds, which deteriorate the electronic properties of the device through surface recombination losses at the amorphous/crystalline silicon interface. Thus, a balance between light absorption and recombination of minority carrier has to be satisfied. This work concerns the study of the optoelectronic properties of a-Si:H/c-Si hetero-junction involving two texturization processes of silicon substrates based on a cupper-assisted etching and a CP4 etching. Obtained results show that the optical properties are more interesting with samples etched in cupper solution. However, the highest effective carriers' lifetime, measured by the photoconductive decay (PCD) and μ W-PCD methods are more interesting in samples etched with a CP4 solution. We confirm these results through the determination of the surface recombination velocity of minority carriers, which was obtained from a developed theoretical procedure and PCD measurements. Therefore, we obtain a recombination velocity of 500 cm.s −1 in the case of the CP4 etching. However, it is three times greater in the case of Cu etching. We discuss these results in link with the morphology of fabricated samples performed with 2D and 3D AFM characterization, as well as surface profiling and RMS values.